PID Control of Main Maneuver for Three-Wheeled Omniwheel Robot - Amri, Syaiful; Muharnis, Muharnis; Syah, Khairudin; Azizul, Azizul; Almubarok, Puja; M.Farhan (Politeknik Negeri Bengkalis, 2024)
The maneuverability and precision of three-wheeled omniwheel robots are essential for effective navigation invarious environments. This study aims to implement a PID (Proportional-Integral-Derivative) control system on a threewheeled omniwheel robot using the arduino platform, with compass sensor data serving as the primary reference fororientation control. The omniwheel design allows the robot to move freely in any direction, making it suitable forapplications that require high flexibility and responsiveness. In this research, mathematical modeling of the robot'sdynamics was conducted to understand its behavior during movement. The PID control algorithm was implemented tomanage the speed and angular velocity of each wheel, utilizing feedback from the compass sensor to maintain the desiredheading and stability during maneuvers. The experimental setup involved various maneuver scenarios, including rapiddirection changes and navigation through complex paths. Results indicate that the integration of PID control withcompass data significantly enhances the stability and accuracy of the robot's maneuvers. The proposed control systemeffectively reduces heading error and improves response time, demonstrating its effectiveness in maintaining precisemovement under dynamic conditions. In conclusion, the combination of Arduino platform, PID control, and compassdata provides a robust solution for controlling the main maneuver of a three-wheeled omniwheel robot, particularly inapplications demanding high maneuverability and directional stability.